Integración de BIM y GIS en proyectos de construcción. (Agosto 2022) - Santacruz, Hector (Artes: Architecture, Technology and Sustainability, 2022)
Historically, most construction projects are based on CAD data, GIS information is only used to evaluate the possible location of the project, which results in the non-use of a large amount of data related to the context of the project. project. GIS information allows us to access environmental, socioeconomic, cultural data, historical information on both pedestrian and vehicular mobility and most importantly, it gives us the understanding, based on precise data, of what the real impact of a project on the environment will be. of its implementation on the site. The BIM methodology is currently one of the most powerful tools for making decisions in complex construction projects based on the information analyzed during each stage of the project life cycle, but by itself, this methodology is not sufficient to understand the impact of a facility within a broader environment such as a region or a city, mainly because BIM focuses only on what happens with the facility and not how it affects its environment, this is where the strength of GIS becomes relevant when being able to use the information generated by BIM and extrapolate it to decision making within an environment that contextualizes several variables that, through specific analysis procedures, allow us to make more efficient planning decisions. In this article, the theoretical definitions will be left aside and the definitions applied to BIM and GIS in construction projects will be reviewed separately, also trying to see how these methodologies would be applied together.